Etiopathogenesis Of Hypocobaltosis In Productive Сows - Abdumajitov; Bakirov (PT. Antis International Publisher, 2024)
The article describes the cause, pathogenesis of hypocabolosis, symptoms and changes in the cicatricial fluid in this pathology in productive cows.